Exploring microbiome-targeted interventions in the mitigation of endothelial dysfunction - Risk, Briana D., author; Weir, Tiffany L., advisor; Gentile, Christopher L., advisor; Chicco, Adam J., committee member; Foster, Michelle T., committee member (Colorado State University. Libraries, 2024)
Cardiovascular disease (CVD) has been the leading cause of mortality in the United States for more than seventy years eclipsing cancer and respiratory disease by more than 13%. Despite sincere efforts to decrease the incidence of CVD, various environmental and intrinsic factors contribute to CVD progression, making it challenging to mitigate this complex condition. However, the past decade has shown tremendous growth in understanding the connection between the gut microbiome in its protective, or pathogenic progression of CVD. The gut microbiome, or the consortia of microbial species, genes, and metabolites, that shapes the gastrointestinal environment has a profound impact on the vascular endothelium through mechanisms not yet entirely understood. Therefore, the purpose of the research in this dissertation was to: 1) Utilize next-generation sequencing and metabolomics to characterize microbial contribution to varied endothelial response after a dietary blueberry intervention in post-menopausal females; 2) Determine if a hypertensive microbiome after blueberry treatment confers gastrointestinal and endothelial phenotype in a humanized mouse model; 3) Evaluate the efficacy of a probiotic in reversing endothelial dysfunction in dietarily obese mice, while exploring the contribution to gut barrier integrity and vasoactive metabolite proliferation in a novel cell co-culture.
Keywords: endothelial dysfunction; gut health; probiotic; fecal transplant; cardiovascular disease; microbiome